2017
DOI: 10.4103/0972-9062.217618
|View full text |Cite
|
Sign up to set email alerts
|

Bovine trypanosomiasis in tsetse-free pastoral zone of the Far-North region, Cameroon

Abstract: Cattle trypanosomiasis has reappeared in the Far-North region and seems to be in the inter-epizootic phase. Pastoralists have a good knowledge of the disease, but their perception of its importance seems to be influenced by the persistence of symptoms attributed to this disease in suspect cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…In several countries there have been reports of AAT in cattle settlements free of tsetse flies, but where biting flies are abundant e.g. northern Nigeria, Cameroon and Chad [8][9][10]. The abundance of biting flies throughout the year is important in the epidemiology of the disease and parasite diversities among livestock hosts [11].…”
Section: Introductionmentioning
confidence: 99%
“…In several countries there have been reports of AAT in cattle settlements free of tsetse flies, but where biting flies are abundant e.g. northern Nigeria, Cameroon and Chad [8][9][10]. The abundance of biting flies throughout the year is important in the epidemiology of the disease and parasite diversities among livestock hosts [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the Far north region of Cameroon, there are no tsetse flies but the area is heavily infested by tabanids and stomoxyines. Suh et al (2017) reported the occurrence of T. vivax in cattle from the Far North region of Cameroon, indicating the important role of mechanical vectors in transmission. The present study identified one species of the genus Chrysops (Chrysops longicornis), one species of the genus Haematopota (Haematopota decora), two species of Tabanus (Tabanus taeniola and Tabanus gratus) and four species of Stomoxys (S. n. niger, S. omega, S. n. bilineatus and S. inornatus).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors report that T. evansi is geographically most widespread trypanosome (Desquesnes et al, 2013) and was originally reported in Camels in Africa (Lun and Brun, 1992). In the tsetse free Far north region of Cameroon, Suh et al (2017) reported 0.67% and 1.46% prevalence of T. vivax. The continuous usage of trypanocides and insecticides in Ngaoundere is an indication of the existence of trypanosomiasis and its mechanical vectors in the apparent absence of glossines.…”
Section: Introductionmentioning
confidence: 98%
“…T. vivax is reported from cattle, dromedary camel, [6], goat, sheep, pig, dog [7], horse, donkey [8], buffalo, warthog, hippopotamus, reedbuck, waterbuck [9], antelope [10], giraffe [11], rhinoceros [12], rodents, pangolin, primates, reptiles and different wild ungulates and carnivores [13]. In Sub-Saharan Africa, T. vivax is mainly transmitted by tsetse ies (Diptera: Glossinidae) in which the parasite can multiply and remain infective throughout the insect's life [14]. The parasite has acquired the ability to be also transmitted mechanically by hematophagous ies like Tabanus spp., Stomoxys calcitrans and Haematobia irritans, which are responsible for the spread of T. vivax in tsetse free areas of Africa and in Latin America [4,[15][16][17][18] T. vivax infection can be suspected by clinical and/or serological evidence and can be con rmed by parasitological or molecular methods [19].…”
Section: Introductionmentioning
confidence: 99%